2004
DOI: 10.1161/01.cir.0000112567.53841.10
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Type 3 Severe von Willebrand Disease Are Not Protected Against Atherosclerosis

Abstract: Background-The results of a number of studies in pigs and mice suggest that absence of von Willebrand factor (vWF) protects against the development of atherosclerosis. We studied whether patients with a complete deficiency of vWF (type 3 von Willebrand disease [vWD]) develop fewer atherosclerotic vessel wall changes than healthy controls. Methods and Results-This study included 47 individuals with type 3 vWD and 84 healthy controls. Early atherosclerotic changes were assessed by measuring the thickness of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 35 publications
6
33
0
Order By: Relevance
“…25 In humans, several earlier studies analyzed the presence of subclinical atherosclerosis by measuring the carotid and femoral intima media thickness (IMT) in patients with hemophilia or von Willebrand disease. [26][27][28][29] Overall, there was no difference in the mean IMT of either the carotid artery (0.75 mm vs 0.74 mm) or femoral artery (0.75 mm vs 0.79 mm) in patients and age-matched healthy controls. 8 Recently, 2 studies investigated whether hypocoagulability is associated with decreased atherogenesis by evaluating subclinical atherosclerosis and endothelial function in hemophilia patients and in matched unaffected controls.…”
Section: Atherosclerosis In Patients With Hemophiliamentioning
confidence: 82%
“…25 In humans, several earlier studies analyzed the presence of subclinical atherosclerosis by measuring the carotid and femoral intima media thickness (IMT) in patients with hemophilia or von Willebrand disease. [26][27][28][29] Overall, there was no difference in the mean IMT of either the carotid artery (0.75 mm vs 0.74 mm) or femoral artery (0.75 mm vs 0.79 mm) in patients and age-matched healthy controls. 8 Recently, 2 studies investigated whether hypocoagulability is associated with decreased atherogenesis by evaluating subclinical atherosclerosis and endothelial function in hemophilia patients and in matched unaffected controls.…”
Section: Atherosclerosis In Patients With Hemophiliamentioning
confidence: 82%
“…67 In contrast to animal models, a clinical study has failed to show protection from atherosclerosis in patients with type 3 VWD who presumably lack WPBs. 68 Interestingly, the 3-hydroxy-3-methylglutaryl coenzyme A (CoA) (3-hydroxy-3-methylglutaryl [HMG]-CoA) reductase inhibitor simvastatin has been shown to decrease regulated exocytosis of WPBs. 69 This mechanism of action of HMG-CoA reductase inhibitors may therefore contribute to the beneficial effects of these reagents in treatment of patients with cardiovascular disease.…”
Section: Conclusion and Remaining Issuesmentioning
confidence: 99%
“…A role for intrinsic pathway factors in arterial disease in humans is not as clear as for venous events. Severe congenital coagulopathies such as hemophilia, 40 type III von Willebrand disease, 41 or Glanzmann thrombasthenia 42 (absence or abnormality of the platelet ␣IIb/␤III integrin) do not appear to affect development of atherosclerosis, although there are suggestions that hemophilia retards arterial plaque formation somewhat in humans 43 and mice. 44 However, longitudinal studies in the Netherlands of patients with factor VIII or factor IX deficiency demonstrated a lower incidence of myocardial infarction than in controls, and an 80% reduction in mortality from coronary artery disease, suggesting factor VIII or IX deficiency may inhibit formation of thrombi at sites of plaque rupture.…”
Section: Intrinsic Pathway Proteins and Thromboembolic Disease In Humansmentioning
confidence: 99%